2011
DOI: 10.1007/s10549-011-1526-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and course of brain metastases in triple-negative breast cancer: comparison with human epidermal growth factor receptor 2-positive and other type at single institution in Korea

Abstract: The incidences and clinical aggressiveness of intracranial metastases have not been as well characterized in patients with triple-negative (TN) breast cancer as in patients with human epidermal growth factor 2-positive (HER2+) breast cancer. Patients diagnosed with brain metastases from primary breast cancer, as determined by computed tomography and/or magnetic resonance imaging, at Asan Medical Center from January 1990 to July 2006 were identified and classified into three subtypes: TN, HER2+, and other. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 32 publications
1
15
0
2
Order By: Relevance
“…The IHC test is described in previous studies. 24,25 Furthermore, the ER and PR statuses were combined and denoted as HR status. For HER2 status, 0 and 11 were considered as negative and 31 as positive by IHC scores.…”
Section: Tumor Subtypes Of Breast Cancermentioning
confidence: 99%
“…The IHC test is described in previous studies. 24,25 Furthermore, the ER and PR statuses were combined and denoted as HR status. For HER2 status, 0 and 11 were considered as negative and 31 as positive by IHC scores.…”
Section: Tumor Subtypes Of Breast Cancermentioning
confidence: 99%
“…TNBC is more aggressive than other breast cancer subtypes, and it is more likely to metastasize at an early stage [2, 3]. TNBC remains the hardest breast cancer subtype to treat because it is a highly heterogeneous disease and lacks effective targets for therapy [2].…”
Section: Introductionmentioning
confidence: 99%
“…Its efficacy has been documented in several studies which suggested that postmenopausal patients, treatment with this agent can expected to yield about 20-30% objective responses. Clinical studies found that MA can improve appetite, increase food intake, promoted protein and fat synthesis of adjuvant chemotherapy in advanced breast cancer patients (Jang et al, 2011;Lara-Medina et al, 2011). MA has a certain degree of protection function of bone marrow and direct treatment of cancer role.…”
Section: Discussionmentioning
confidence: 99%